Theoretical study and design of multifunctional phosphorescent platinum(ii) complexes containing triarylboron moieties for efficient OLED emitters. Issue 4 (10th December 2014) - Wu, Yong; Shan, Guo-Gang; Li, Hai-Bin; Wu, Shui-Xing; Ren, Xin-Yao; Geng, Yun; Su, Zhong-Min
Abstract : TD-DFT including SOC calculations were employed to evaluated the Φ PL of phosphorescence OLED emitters. Abstract : The geometries, electronic structures, photophysical properties and spin–orbit coupling (SOC) effects in the radiative process for the recently synthesized complexes (Bppy)Pt(acac) (1 ) and (BNppy)Pt(acac) (2 ) as well as the designed complexes3–6 were investigated by DFT and TD-DFT calculations, to reveal the influences of the functional ligands on charge injection ability and phosphorescence efficiency of emitters. It is found that compared with electron acceptor complex1, complexes2–6 have lower ionization potentials and comparable high electronic affinities, which are suited for bipolar luminescent materials. The results also demonstrated that Bppy complexes1, 5 and6 have more 3 MLCT compositions in T1 emitting states compared with BNppy complexes2–4, which results in strong SOC and fast k r . Thus, the phosphorescence efficiency of1 is higher than that of2 . In addition, 5 and6 have the balanced charge transport and better hole injection ability when the hole-transporting ligand is incorporated to1 . Therefore, 5 and6 can server as promising candidates for efficient multifunctional phosphorescent OLED emitters owing to their ambipolar characters, balanced charge carrier injection/transport features and high phosphorescence quantum efficiency.